PENGARUH HASIL BELAJAR PENGANTAR AKUNTANSI TERHADAP TINGKAT PEMAHAMAN AKUNTANSI MAHASISWA FAKULTAS EKONOMIKA DAN BISNIS DI UNIVERSITAS KRISTEN SATYA WACANA DENGAN MOTIVASI BELAJAR SEBAGAI VARIABEL MODERASI - Dianita Ayu Restiningtyas; Paskah Ika Nugroho (Politeknik Ganesha Medan, 2023)
The purpose of this study is to determine the role of moderation of learning motivation in the influence of introductory accounting learning outcomes on the level of understanding of accounting. The sample taken was students of the Faculty of Economics and Business who had taken 10 courses of the Quality Earth Peg (PBMt). The results of data analysis are known that simultaneously all free variables together do not have a significant influence on bound variables, where the results of introductory accounting learning, learning motivation and interaction between the two together have no influence on the level of understanding of accounting. While partially obtained, (1) the results of learning introduction to accounting do not affect the level of understanding of accounting, (2) there is no influence of the results of learning introduction to accounting on the level of understanding of and there is no influence of learning motivation results on the level of understanding of accounting,(3) introductory accountinglearning outcomes,learning motivation and interaction between the two have no effect on the level of understanding of accounting.